ความชุกของปัญหาสุขภาพจากการทำงานในบุคลากรห้องปฏิบัติการทางการแพทย์ที่ปฏิบัติงานในโรงเรียนแพทย์แห่งหนึ่ง - อมตา อุตมะ (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
The purpose of this cross-sectional descriptive study was to determine the prevalence and factors that related to work accident, general health problems by chemicals exposure, musculoskeletal disorder and job stress in biomedical laboratory workers in medical school. Data were collected by self-administered questionnaires during November to December 2008. The study sample included 162 workers at 13 biomedical laboratories throughout the medical school. The results showed that the prevalence of work accidents was 30.0%. The prevalence of abnormal symptoms form chemicals exposure were the effects on skin (46.7%), eye (28.7%), respiratory system (18.0%) and nervous system (18.0%) respectively. Factors that related to health problem were work duration per years and exposure frequency per week (p<0.05). The prevalence of musculoskeletal disorders was 42.7%, the three most persistent musculoskeletal disorders were upper back 29.2%, neck 28.6% and left shoulder 23.8% respectively. Factors that related to musculoskeletal disorders were work time, uncomfortable posture, and repetitive movement; prolong computer usage, attitude of high job demand and low job control (p<0.05). The prevalence of job stress was 17.9%. Factors that related to job stress were age, work duration and experience of work accidents from biological hazard (p<0.05). In conclusion, this study showed the most work-related health problem in biomedical laboratories workers were health problem due to chemicals exposure, musculoskeletal disorder, work accidents and job stress respectively. The related departments should give precedence and pay attention to group of workers with these problems. Furthermore, detailed examination of their related factors will be helpful for their prevention planning.